Late Onset Bipolar Disorder due to a Lacunar State - Elena Antelmi; Margherita Fabbri; Lucia Cretella; Maria Guarino; Andrea Stracciari (Behavioural Neurology)
Objective. To describe a patient with a new onset bipolar disorder (BD) type II, secondary to a lacunar state. Background. Poststroke BD is rare and mainly associated with lesion in the prefrontal-striatal-thalamic circuit. Materials and Methods. A 51-year-old woman came to our attention for a mood disorder of recent onset. At 49, she had suffered acute left-sided limb weakness that improved spontaneously four days later. Arterial hypertension was subsequently diagnosed. After 6 months, she began to suffer from alternating brief periods of expansive and elevated mood with longer periods of depressed mood, with a suicide attempt. We performed extensive laboratory and instrumental investigations, as well as, psychiatric consultation, and a cognitive assessment, which was repeated 9 months later. Results. Brain magnetic resonance disclosed leukoaraiosis and a lacunar state of the basal ganglia. Transcranial Doppler showed a patent foramen ovale. A psychiatric consultation led to the diagnosis of BP type II. Neuropsychological evaluation detected deficits in attention/executive functions, verbal fluency, and memory. Nine months later, after specific psychiatric therapy, the psychiatric symptoms were remarkably improved. Conclusion. Our case sheds light on the role of the basal ganglia in mood disorders and the importance of ruling out brain injury in late onset BP.